Literature Review: Government Policies on the Development of Teaching Personnel and Educational Institutions - Arhas, Sitti Hardiyanti; Wahira, Wahira (ASHA Publishing, 2025)
This literature review analyzes the impact of government policies on the improvement of teaching staff and educational institutions in developing countries. This study examines the impact of strategic government actions on the quality of education by drawing on a wealth of academic resources. Studies show that effective teacher development requires consistent investment in professional development, cohesive policy frameworks, and institutional capacity building. Additionally, utilizing technology and adhering to international educational standards is becoming increasingly important. However, these things must be carefully adjusted to fit the local school to be effective. The review emphasizes that context-sensitive, inclusive, and equitable policy approaches are more effective in addressing the specific problems facing education systems in developing countries. This assessment uses a qualitative method. It also reveals that the implementation of current policies has shortcomings, including the need for an equitable distribution of resources and significant stakeholder involvement. These findings underscore the importance of developing educational strategies that align with global trends by focusing on addressing local contexts and needs. This review supports adaptive and collaborative governance models to facilitate the development of teaching capacity and sustainable institutional development in the evolving educational context.